2000
DOI: 10.1258/002367700780457572
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fats influence consumption and metabolic measures in male and female laboratory mice

Abstract: SummaryJuvenile and adult male and female Swiss mice in metabolism cages were fed one of four specially-formulated, pelleted diets containing respectively 8% saturated vegetable fat, 8% soya oil, 8% olive oil and 2 % soya oil. The identities of the diets were hidden from the experimenter. Subjects were individually housed in metabolism cages and their consumption of food, growth and eliminative activities were measured. Clearly, these non-isocaloric diets differed in palatability, producing complex effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The modest body weight gain in these subjects may be due to the low-fat content of that diet (which would reduce its calori c content). Other studies on the same mice (Brain et al 2000) have shown that these non-isocalori c diets differed in palatability, producing complex effects on growth as well as metabolic measures. Many of these physiological indices were in uenced by age, sex and duration of dietary exposure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The modest body weight gain in these subjects may be due to the low-fat content of that diet (which would reduce its calori c content). Other studies on the same mice (Brain et al 2000) have shown that these non-isocalori c diets differed in palatability, producing complex effects on growth as well as metabolic measures. Many of these physiological indices were in uenced by age, sex and duration of dietary exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, the mice in the present study could 'self dose' themselves with different quantities of the varied diets on the basis of their preferences. These preferences might be in uenced by age, sex and duration of exposure (Brain et al 2000).…”
Section: Discussionmentioning
confidence: 99%